The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-4632.2009.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of acne vulgaris on the quality of life and psychologic status in patients from upper Egypt

Abstract: Acne vulgaris has a significant effect on the quality of life. Our results highlight the importance of recognizing psychiatric comorbidity in acne patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
10
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 20 publications
5
62
10
5
Order By: Relevance
“…This finding coincides with what has been reported in the Iranian study which has revealed that acne affected quality of life of 51.8% with mean score of DLQI was 6.42 (25). On the other hand, in a study by Abdel-hafez in Egypt, the mean DLQI score was 11.9 and 15.0 in female and male subjects, respectively, which are worse compared to the results of our study (26). In a study by Walker (22), performed on students in Scotland, the mean scores of DLQI and CADI were, respectively, 1.7 and 1.9 and the quality of life of patients was better, when compared to the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding coincides with what has been reported in the Iranian study which has revealed that acne affected quality of life of 51.8% with mean score of DLQI was 6.42 (25). On the other hand, in a study by Abdel-hafez in Egypt, the mean DLQI score was 11.9 and 15.0 in female and male subjects, respectively, which are worse compared to the results of our study (26). In a study by Walker (22), performed on students in Scotland, the mean scores of DLQI and CADI were, respectively, 1.7 and 1.9 and the quality of life of patients was better, when compared to the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…An Indian study showed that 57% of patients reported negative effect of acne on work/study (20). Twenty-one percent of pupils felt that acne affected their schoolwork and personal activities (26). Similar findings were also reported by Walker and Lewis-Jones (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DLQI was designed for patients aged 16 or above, and the CDLQI for those aged between 4 and 16. Both the DLQI and CDLQI have been extensively validated, but only the DLQI has been used in low and middle Income countries, including sub-Sahara Africa [9], [16], [20], [21]. Both the DLQI and CDLQI were translated into the local language, Twii, according to the instructions of the authors of the original questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Its prevalence among those aged 12 to 24 years is estimated to be 85%, although it can persist beyond young adulthood despite treatment. [3][4][5] Acne can adversely affect quality of life [6][7][8][9][10][11][12][13] and may lead to emotional distress and physical scarring. 14,15 The clinical presentation of acne ( Figure 1) varies from primarily comedonal to mixed comedonal and inflammatory acne.…”
mentioning
confidence: 99%